On the Exploitation of 5G Multi-Access Edge Computing for Spatial Audio in Cultural Heritage Applications - Claudia Rinaldi (IEEE, 2021)
This work presents a service for the improvement of cultural heritage experiences, which exploits the advantages coming from the 5G paradigm. Indeed, in a scenario where many users need to be served by a real-time solution which is in turn required to work on different devices, the potentialities of 5G technology show their suitability. In particular, moving the computation to the edge of the network ensures the availability of resources needed for binaural spatial audio rendering in an independent fashion with reference to the client device and at the same time it guarantees real-time availability of this data since the core network, with its impairments, is not involved. This work demonstrates how 5G could be a critical enabler for delivering low latency services at guaranteed levels, data-centric services, differentiated customer experiences, improved security and reduced costs to the users.